Grammatical errors in specific language impairment: competence or performance limitations? - Bishop, D (Cambridge University Press, 1994)
Speech samples from twelve 8- to 12-year-old children with specific language impairment (SLI) were analyzed. The feature deficit hypothesis maintains that SLI children may produce morphological markers (e.g. plural -s) correctly, but they do not appreciate their role in marking grammatical features. Rather, they treat them as meaningless phonological variants. Findings from the present study were incompatible with this hypothesis: (a) production of morphological markesr was not random; errors were unidirectional, in almost all cases involving omission of an inflection in an obligatory context; (b) overregularization errors were sometimes observed; (c) grammatical features differed in difficulty; (d) substitution of stems for inflected forms occurred with irregular as well as regular verbs; and (e) errors of pronoun case marking were common and always involved producing an accusative form in a context demanding the nominative. Children who used a specific inflectional form correctly in some utterances omitted it in others, suggesting a limitation of performance rather than competence. There were few obvious differences between utterances that did and did not include correctly inflected forms, though there was a trend for grammatical errors to occur on words that occurred later in an utterance. It is suggested that slowed processing in a limited capacity system that is handling several operations in parallel may lead to the omission of grammatical morphemes.